Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1093/infdis/170.4.854
|View full text |Cite
|
Sign up to set email alerts
|

Fca Receptor Iia (Cd32) Heterogeneity In Patients With Recurrent Bacterial Respiratory Tract Infections

Abstract: Fc gamma RIIa (CD32) is the sole IgG Fc receptor capable of interaction with human IgG2, the main IgG subclass of bacterial capsular polysaccharides. The two genetically determined allotypes of human Fc gamma RIIa, Fc gamma RIIa-R131 and IIa-H131 alleles, have functionally different reactivities with human IgG2. The capacity of polymorphonuclear leukocytes (PMNL) homozygous for Fc gamma RIIa-H/H131 for IgG2 opsonized bacteria is significantly higher than phagocytosis by PMNL homozygous for Fc gamma RIIa-R/R131… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
102
1
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(114 citation statements)
references
References 0 publications
8
102
1
3
Order By: Relevance
“…Consistent with our findings, previous studies have shown an increased susceptibility to bacterial infections by encapsulated bacteria in patients with the R/R genotype of FcgRIIA 18,35 and it has been reported that the frequency of both heterozygous FcgRIIA H/R and homozygous R/R was higher in patients with recurrent bacterial respiratory tract infections than in controls. 18 However, the lack of difference in the frequency of FcgRIIA genotypes in CF patients and control subjects observed in this study and the lack of association between these genotypes and other parameters of disease severity, as well as the contribution of other variables to the increased risk of acquiring P. aeruginosa infection, support the concept that the severity of pulmonary involvement in CF is controlled by multifactorial genetic mechanisms and suggest that other genetic factors may influence susceptibilities and outcomes in which Fcg receptors play a role.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our findings, previous studies have shown an increased susceptibility to bacterial infections by encapsulated bacteria in patients with the R/R genotype of FcgRIIA 18,35 and it has been reported that the frequency of both heterozygous FcgRIIA H/R and homozygous R/R was higher in patients with recurrent bacterial respiratory tract infections than in controls. 18 However, the lack of difference in the frequency of FcgRIIA genotypes in CF patients and control subjects observed in this study and the lack of association between these genotypes and other parameters of disease severity, as well as the contribution of other variables to the increased risk of acquiring P. aeruginosa infection, support the concept that the severity of pulmonary involvement in CF is controlled by multifactorial genetic mechanisms and suggest that other genetic factors may influence susceptibilities and outcomes in which Fcg receptors play a role.…”
Section: Discussionsupporting
confidence: 93%
“…16,17 The FcgRIIA-H/R genotype has been associated to the risk of infection by encapsulated organisms. 18,19 In studies using IgG2-opsonized encapsulated bacteria, phagocytosis by FcgRIIA-HH PMN was significantly higher than in FcgRIIA-RR PMN, which poorly ingested IgG2 opsonized bacteria. 19 -20 FcgRII has also been shown to play a role in the pathophysiology of autoimmune diseases and polymorphisms within this gene have been reported to be associated with the risk or severity of autoimmune disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The polymorphism at amino acid 131, which changes the IgG binding specificity of FcgRIIA, has been implicated in both infectious and autoimmune diseases. 12,13,20,21 Shown in Table 2 are the results of the FcgRIIA-131 genotyping from RA patients and normal controls. No differences in the frequency of FcgRIIA-131R or FcgRIIA-131H genotypes were observed between the normal donors and the RA subjects, which is consistent with previous reports.…”
Section: Clinical Features Of Ra Patients In This Studymentioning
confidence: 99%
“…19 In general, these polymorphisms have been shown to alter the ligand binding specificity of particular FcgR, such as FcgRIIa, 17 and FcgRIIIa. 14,16 These allelic polymorphisms have proved to be clinically significant in infectious 20,21 and autoimmune 12,13,[22][23][24] diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The gene that encodes FcgRIIa, FCGR2A (1q23), is predominantly expressed on neutrophils and carries a functional SNP that substitutes an arginine (R) to histidine (H) at position 131. Compared with wildtype 131R homozygotes, 131 homozygotes have high binding affinity for IgG2 and have been associated with a number of infectious [46][47][48] and autoimmune diseases. 49,50 Given that MM is characterized, in part, by an accumulation of IgG-producing monoclonal plasma cells, it is possible that variants in FCGR2A may contribute either directly or indirectly to the genetic susceptibility profile associated with the etiology of this B-cell malignancy.…”
Section: Discussionmentioning
confidence: 99%